Study of the antitumour effects and the modulation of immune response by histamine in breast cancer - Nicoud, Melisa Beatriz (2020)
Fil: Nicoud, Melisa Beatriz. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas. Laboratorio de Biología Tumoral e Inflamación; Argentina